LINEAR CONGRUENT METHOD Penerapan Algoritma Linear Congruent Method Pada Pengacakan Soal Kenaikan Tingkat Karyawan Di LKP Sempoa SIP Binjai - Adhitya, Sri Ayu; Ginting, Budi Serasi; Sihombing, Marto (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2022)
An exam is a test conducted to see and determine a person's ability in terms of competence,knowledge and experience. By conducting an exam, an educational institution can determinewhether a student can continue to the next class or not, while in a work environment, theinstitution can determine whether a person is entitled to be accepted as a worker or can get apromotion. Based on the journal Andilala, Gunawan (2018) about the implementation of thelinear congruent method for randomizing questions in an android-based arithmetic calculationgame. Said that "The linear congruent method is used as a means for randomizing thearithmetic calculation questions so that users who play will not find the same questions asother users". In conducting exams or tests for employees, SIP Sempoa still uses the manualmethod where all employees take exams with the same paper and number of questions. Theimplementation of the exam with the same number of questions is considered ineffective fordetermining employee competence. To avoid this problem, the author will utilize technologyby using the Linear Congruent Method (LCM) to generate a random number of questions sothat each employee has a question with a different number and process. exams are moreeffective. Based on the explanation above, the author takes the title "Application of the LinearCongruent Method Algorithm in Randomization of Employee Level Increase Problems at LKPAbacus SIP Binjai".